(untitled) (American Journal of Islam and Society, 2018)
Professor Feldmeier’s thoughtful response provides a useful context for considering both Lomellini’s work and the undertakings of seventeenth century Jesuits more generally. Jesuits such as De Nobili and Ricci were exceptional and deeply engaged with the cultures with which they dialogued. Far more Jesuits were like Lomellini and knew what they believed to be true about other faith traditions from informants or books. Since these Jesuits helped shape European perceptions of Islam, we need to learn more about how they understood that faith, and their own faith as well.